2014
DOI: 10.1158/0008-5472.can-13-3021
|View full text |Cite
|
Sign up to set email alerts
|

Ly49 Family Receptors Are Required for Cancer Immunosurveillance Mediated by Natural Killer Cells

Abstract: According to the missing-self hypothesis, natural killer (NK) cells survey for target cells that lack MHC-I molecules. The Ly49 receptor family recognizes loss of MHC-I and is critical for educating NK cells, conferring the ability to eliminate transformed or infected cells. In this study, we evaluated their requirement in innate immune surveillance of cancer cells using genetically manipulated mice with attenuated expression of Ly49 receptors (NKC KD ) in several models of carcinoma and metastasis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…47 Killer cell lectin-like receptor, subfamily A, member 3 (Klra3) is an NK-cell receptor that is required for activation. Major histocompatibility complex class I recognition receptor (Ly49I, Klra9) serves as an NK-cell activator 48 and is involved in controlling cytomegalovirus infection. 49 The reduction in receptors for NK-cell activation would explain the higher degree of lung carcinoma development in RAG1 −/− Sgo1 −/+ animals, because of reduced NK-cell-mediated surveillance for mutagenic CIN cells.…”
Section: Resultsmentioning
confidence: 99%
“…47 Killer cell lectin-like receptor, subfamily A, member 3 (Klra3) is an NK-cell receptor that is required for activation. Major histocompatibility complex class I recognition receptor (Ly49I, Klra9) serves as an NK-cell activator 48 and is involved in controlling cytomegalovirus infection. 49 The reduction in receptors for NK-cell activation would explain the higher degree of lung carcinoma development in RAG1 −/− Sgo1 −/+ animals, because of reduced NK-cell-mediated surveillance for mutagenic CIN cells.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of Ly49 in NK cell-mediated tumor immunosurveillance and MHC I-directed tumor editing was recently demonstrated in a study using Ly49-deficient mice (101). Another study demonstrated that human tumors reduced activating NK cell receptor (NKp30) recognition by NK cells by shedding B7-H6 from their cell surface (102).…”
Section: Other Parameters Impacting Cd8 + T Cells In Cancer Immunoedimentioning
confidence: 99%
“…37 The Ly49 family of receptors is known to help in NK cell education, licensing to control cancer growth and immunosurveillance. 38 Furthermore, Ly49H C NK cells have been implicated to differentiate into long-lived memory NK cells during MCMV infection and provide better protection to the host. 39 Our data showing significantly reduced Ly49D and Ly49H expression in tumor infiltrating CD27 C…”
Section: Cd11bmentioning
confidence: 99%